Insights into the Relationship between Toll Like Receptors and Gamma Delta T Cell Responses - Dar, Asif Amin; Patil, Rushikesh Sudam; Chiplunkar, Shubhada Vivek (Frontiers in Immunology, 2014)
The tumour microenvironment is an important aspect of cancer biology that contributes to tumour initiation, tumour progression and responses to therapy. The composition and characteristics of the tumour microenvironment vary widely and are important in determining the anti-tumour immune response. Successful immunization requires activation of both innate and adaptive immunity. Generally immune system is compromised in patients with cancer due to immune suppression, loss of tumour antigen expression, and dysfunction of antigen presenting cells (APC). Thus therapeutic immunization leading to cancer regression remains a significant challenge. Certain cells of the immune system, including dendritic cells (DCs) and γδ T cells are capable of driving potent anti-tumour responses. The property of MHC-unrestricted cytotoxicity, high potential of cytokine release, tissue tropism and early activation in infections and malignant disease makes γδ T cells as an emerging candidate for immunotherapy. Various strategies are being developed to enhance anti-tumour immune responses of γδ T cells and dendritic cells one of them is the use of novel adjuvants like TLR agonists which enhance γδ T cell function directly or through DC activation which has ability to prime γδ T cells. TLR agonists are being used clinically either alone or in combination with tumour antigens and has shown initial success in both enhancing immune responses and eliciting anti-tumour activity. TLR activated γδ T cells and dendritic cells nurture each other’s activation. This provides a potent base for first line of defense and manipulation of the adaptive response against pathogens and cancer. The available data provides a strong rational for initiating combinatorial therapy for the treatment of diseases and this review will summarize the application of adjuvants (TLRs) for boosting immune response of γδ T cells to treat cancer and infectious diseases and their use in combinatorial therapy.